2004
DOI: 10.1177/039139880402701203
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Acute Renal Failure following Ischemia/Reperfusion

Abstract: Acute renal failure (ARF) necessitating renal replacement therapy is a common problem associated with high morbidity and mortality in the critically ill. Hypotension, followed by resuscitation, is the most common etiologic factor, mimicked by ischemia/reperfusion (I/R) in animal models. Although knowledge of the pathophysiology of ARF in the course of this condition is increasingly detailed, the intracellular and molecular mechanisms leading to ARF are still incompletely understood. This review aims at describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
66
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 80 publications
1
66
0
Order By: Relevance
“…6 IRI is a complex event initiated by renal ischemia, leading to adenosine triphosphate (ATP) depletion and impairment of cellular polarity and cytoskeletal structure. 7 Subsequent reperfusion potentiates this damage by initiating a robust inflammatory response and release of reactive oxygen species (ROS), contributing to necrosis and apoptosis of renal tubular cells and renal dysfunction. 8,9 Multiple studies have previously demonstrated that prolonged warm ischemia time (WIT) during PN causes residual renal tissue injury, is severely detrimental to postoperative renal function and can result in new onset chronic kidney disease (CKD).…”
Section: Introductionmentioning
confidence: 99%
“…6 IRI is a complex event initiated by renal ischemia, leading to adenosine triphosphate (ATP) depletion and impairment of cellular polarity and cytoskeletal structure. 7 Subsequent reperfusion potentiates this damage by initiating a robust inflammatory response and release of reactive oxygen species (ROS), contributing to necrosis and apoptosis of renal tubular cells and renal dysfunction. 8,9 Multiple studies have previously demonstrated that prolonged warm ischemia time (WIT) during PN causes residual renal tissue injury, is severely detrimental to postoperative renal function and can result in new onset chronic kidney disease (CKD).…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Hypoxia, ischemia reperfusion (IR) injury, and oxidative stress damage are common pathologic assaults that inflict injury on epithelial cells, and the endurance of these cells strongly influences the clinical outcome. 7,8 Cell adhesion plays a major role in kidney injury and repair. In response to insults such as ischemia or toxins, kidney epithelial cells lose their cellecell and cellematrix interactions, leading to loss of cell polarity, increased permeability, and cell death.…”
mentioning
confidence: 99%
“…Polarized epithelial cells are susceptible to acute toxic and ischemic injury (4,5), which is accompanied by alterations in both cell-cell and cell-matrix adhesions and results in loss of cell polarity (6). This loss of cell polarity is responsible for the redistribution of integrin subunits from the basolateral to the apical membrane and contributes to the shedding of cells from the supporting basement membrane (7)(8)(9).…”
mentioning
confidence: 99%